Characterization of Cardiopulmonary Interactions and Exploring Their Prognostic Value in Acute Bronchiolitis: A Prospective Cardiopulmonary Ultrasound Study - Moises Rodriguez-Gonzalez; Patricia Rodriguez-Campoy; Ana Estalella-Mendoza; Ana Castellano-Martinez; Jose Carlos Flores-Gonzalez (Tomography, 2022)
We aimed to delineate cardiopulmonary interactions in acute bronchiolitis and to evaluate the capacity of a combined cardiopulmonary ultrasonography to predict the need for respiratory support. This was a prospective observational single-center study that includes infants <12 month of age admitted to a hospital due to acute bronchiolitis. All the included patients underwent clinical, laboratory and cardiopulmonary ultrasonographic evaluation at the same time point within 24 h of hospital admission. The existence of significant correlation between cardiac and respiratory parameters was the primary outcome. The association of different cardiopulmonary variables with the need of respiratory support higher than O2, the length of stay hospitalization, the PICU stay and the duration of respiratory support were a secondary outcome. We enrolled 112 infants (median age 1 (0.5–3) months; 62% males) hospitalized with acute bronchiolitis. Increased values of the pulmonary variables (BROSJOD score, pCO2 and LUS) showed moderate correlations with NT-proBNP and all echocardiographic parameters indicative of pulmonary hypertension and myocardial dysfunction (Tei index). Up to 36 (32%) infants required respiratory support during the hospitalization. This group presented with higher lung ultrasound score (p < 0.001) and increased values of NT-proBNP (p < 0.001), the Tei index (p < 0.001) and pulmonary artery pressures (p < 0.001). All the analyzed respiratory and cardiac variables showed moderate-to-strong correlations with the LOS of hospitalization and the time of respiratory support. Lung ultrasound and echocardiography showed a moderate-to-strong predictive accuracy for the need of respiratory support in the ROC analysis, with the AUC varying from 0.74 to 0.87. Those cases of bronchiolitis with a worse pulmonary status presented with a more impaired cardiac status. Cardiopulmonary ultrasonography could be a useful tool to easily identify high-risk populations for complicated acute bronchiolitis hospitalization.